Timing of food intake impacts daily rhythms of human salivary microbiota: a randomized, crossover study. Issue 4 (5th January 2018) - Collado, María Carmen; Engen, Phillip A.; Bandín, Cristina; Cabrera‐Rubio, Raúl; Voigt, Robin M.; Green, Stefan J.; Naqib, Ankur; Keshavarzian, Ali; Scheer, Frank A. J. L.; Garaulet, Marta
Abstract : The composition of the diet (what we eat) has been widely related to the microbiota profile. However, whether the timing of food consumption (when we eat) influences microbiota in humans is unknown. A randomized, crossover study was performed in 10 healthy normal‐weight young women to test the effect of the timing of food intake on the human microbiota in the saliva and fecal samples. More specifically, to determine whether eating late alters daily rhythms of human salivary microbiota, we interrogated salivary microbiota in samples obtained at 4 specific time points over 24 h, to achieve a better understanding of the relationship between food timing and metabolic alterations in humans. Results revealed significant diurnal rhythms in salivary diversity and bacterial relative abundance ( i.e ., TM7 and Fusobacteria) across both early and late eating conditions. More importantly, meal timing affected diurnal rhythms in diversity of salivary microbiota toward an inverted rhythm between the eating conditions, and eating late increased the number of putative proinflammatory taxa, showing a diurnal rhythm in the saliva. In a randomized, crossover study, we showed for the first time the impact of the timing of food intake on human salivary microbiota. Eating the main meal late inverts the daily rhythm of salivary microbiota diversity which may have a deleterious effect on the metabolism of the host.— Collado, M. C., Engen, P. A., Bandíín, C., Cabrera‐Rubio, R., Voigt, R. M., Green, S. J., Naqib, A., Keshavarzian, A., Scheer, F. A. J. L., Garaulet, M. Timing of food intake impacts daily rhythms of human salivary microbiota: a randomized, crossover study. FASEB J. 32, 2060–2072 (2018). www.fasebj.org